A 3-year Longitudinal Study on Interaction Effects Between Self-perceived Weight Status and Lifestyle Behaviors on Obesity: The Children Obesity Study in China Mega-cities (P21-044-19). (13th June 2019) - Ma, Lu; Gao, Liwang; Xue, Hong; Min, Jungwon; Wang, Huijun; Wang, Youfa
Abstract: Objectives: This study examined Chinese children's self-perceived and measured weight status, the main and interaction effects of children's self-perceived weight status and lifestyle behaviors on changes in their body mass index (BMI) over 3 years. Methods: Children's weight, height, self-perceived weight status, and lifestyle behaviors (food intake, sedentary behavior, off-campus physical activity) were measured for 3298 children aged 6–18 years in Beijing, Shanghai, Xian, Nanjing, and Chengdu across China in 2015, 2016 and 2017. This analysis included the 1691 children who had >= two repeated BMI measurements during 2015–2017. Results: The self-perceived weight status of half (49.9% of boys' and 51.3% of girls') was consistent with that based on measured weight and height; 45.2% of boys and 29.8% of girls underestimated their weight status. Boys were more likely to self-perceive as having a normal weight even when being obese. In longitudinal analysis, self-perceived weight status was positively associated with BMI among children (β = 4.99, P  < 0.01), however, neither the lifestyle behaviors were significantly associated with BMI. Significant interactions between self-perceived weight status and lifestyle behaviors were only found among girls, not in boys. Additive interaction between self-perceived weight status and off-campus physical activity was statistically significant in girls (attributable proportion (95%CI) = 0.404 (0.143, 0.666)). Conclusions: In China, it is common children underestimated their own weight status. This leads to subsequent increased BMI. Off-campus physical activity could moderate the association. Future interventions are needed to empower children to have accurate assessment of their weight status and to promote physical activity. Funding Sources: The US National Institutes of Health (NIH U54HD070725).